2016
DOI: 10.1177/0969733016650993
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual well-being and moral distress among Iranian nurses

Abstract: Background: Moral distress is increasingly recognized as a problem affecting healthcare professionals, especially nurses. If not addressed, it may create job dissatisfaction, withdrawal from the moral dimensions of patient care, or even encourage one to leave the profession. Spiritual well-being is a concept which is considered when dealing with problems and stress relating to a variety of issues. Objective: This research aimed to examine the relationship between spiritual well-being and moral distress among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 49 publications
5
46
1
Order By: Relevance
“…This finding can be partially explained by the fact that women tend to experience more emotionally sensitive situations, and, as a result, their level of distress may increase. However, it has to be taken into account that nursing is largely a female profession (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…This finding can be partially explained by the fact that women tend to experience more emotionally sensitive situations, and, as a result, their level of distress may increase. However, it has to be taken into account that nursing is largely a female profession (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…In Iranian studies, no tool is generated to assess the distress specific to Iranian society and culture, and studies are mainly conducted based on Jameson tools 1992 (35), Corley edited the version of 1995 (19,25), 2001 (21,26), 2002 (20,29), and 2005 (11,32). These tools were adjusted by Iranian researchers for Iranian culture in years (1,3,5,11,14,15,(25)(26)(27)(28)(29)(30)(31)(32)(34)(35)(36)(37)(38)(39)(40)(41). Studies in Iran have manipulated the number of Likert scales and in Likert 3, 4, 5, 6, and 7, they have reported that this makes it difficult to compare the results (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…36,38 Psychological impacts included helplessness, feelings of inadequacy, hopelessness, anger, sadness, stress, anxiety, depression, regret, and guilt. 35,36,38,39 Feelings of worthlessness and losing faith are spiritual dimensions affected by moral distress as described by Shoorideh et al, 38 although Soleimani et al 30 did not find a correlation between moral distress and spiritual well-being. Nurses in Shoorideh et al's 38 study expressed that moral distress made them feel that life is meaningless and human beings are worthless.…”
Section: Outcomes Of Moral Distressmentioning
confidence: 98%